Gender differences in entrepreneurial equity financing—a systematic literature review - Kevin Koziol; Maja Schmitz; Suleika Bort (Small Business Economics, 2025)
A growing body of literature explores whether and why female and male entrepreneurs differ in their access to equity financing. This trend has led to an increasing fragmentation of the research field, as many studies analyze various mechanisms and focus on a certain form of equity financing. To advance research on gender differences in equity financing, it is necessary to identify patterns and inconsistent findings in the literature related to these mechanisms. Therefore, we perform a systematic literature review to provide an overview of the current state of knowledge on gender differences in the key forms of entrepreneurial equity financing (venture capital, angel investment, and equity crowdfunding). Based on 75 studies from 2001 to mid-2024, our review indicates that male entrepreneurs have an advantage in raising capital from venture capitalists and business angels, whereas female entrepreneurs are more successful in equity crowdfunding. These gender differences stem from a complex combination of mechanisms, which we categorize into four thematic dimensions that capture entrepreneurs' characteristics, investors' characteristics, the ventures' characteristics and strategies, and contextual factors. We propose specific future research directions for each dimension, and discuss theoretical and methodological research opportunities that are applicable across dimensions to improve our understanding of gender differences in equity financing.
Keywords: G23; G29; J16; L26; M13; 330; Equity financing; Gender; Entrepreneurship; Systematic literature review